2021
DOI: 10.1016/j.fas.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic subtalar ligaments have a consistent presence, location and morphology

Abstract: Background: Chronic subtalar instability is a disabling complication after acute ankle sprains. Currently, the literature describing the anatomy of the intrinsic subtalar ligaments is limited and equivocal which causes difficulties in diagnosis and treatment of subtalar instability.The purpose of this study is to assess the anatomical characteristics of the subtalar ligaments and to clarify some points of confusion. Methods: In 16 cadaveric feet, the dimensions and locations of the subtalar ankle ligaments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
(73 reference statements)
1
21
1
Order By: Relevance
“…Interosseous TC ligament in the control group had a mean thickness of 1.30 mm and a mean width of 1.41 mm. Thickness of ITCL in our study was within the reported range of 1.1 to 3.0 mm in previous cadaveric studies, whereas width of ITCL was far narrower than the reported range of 5.6 to 11.0 mm 10,11,39,40 . The narrow ITCL width in this study might be explained by the fact that only the main fibers of ITCL that were clearly visualized on MRI were measured.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Interosseous TC ligament in the control group had a mean thickness of 1.30 mm and a mean width of 1.41 mm. Thickness of ITCL in our study was within the reported range of 1.1 to 3.0 mm in previous cadaveric studies, whereas width of ITCL was far narrower than the reported range of 5.6 to 11.0 mm 10,11,39,40 . The narrow ITCL width in this study might be explained by the fact that only the main fibers of ITCL that were clearly visualized on MRI were measured.…”
Section: Discussionsupporting
confidence: 73%
“…Thickness of ITCL in our study was within the reported range of 1.1 to 3.0 mm in previous cadaveric studies, whereas width of ITCL was far narrower than the reported range of 5.6 to 11.0 mm. 10,11,39,40 The narrow ITCL width in this study might be explained by the fact that only the main fibers of ITCL that were clearly visualized on MRI were measured. Previous studies using 3D isotropic MRI showed relatively similar results to our study, ranging from 2.68 to 2.85 mm.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, among the ligamentous structures of the subtalar joint, only the footprint area of the ITCL showed significantly higher values in the Degeneration (+) group compared to the Degeneration (-) group for the subtalar joint facet. Previous studies have suggested that the CL, ITCL, and ACaL in the subtalar joint are each important for stability of the subtalar joint [12,15,16]. In addition, the main function of the ITCL has been considered to be connection of the talus and calcaneus and maintenance of the subtalar joint axis [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The ligaments involved in the braking of the subtalar joint include the calcaneofibular ligament [12,13], cervical ligament (CL) [14,15], interosseous talocalcaneal ligament (ITCL) [15][16][17], and anterior capsular ligament (ACaL) [15][16][17]. The calcaneofibular ligament is reportedly important in braking the subtalar joint, but the CL, ITCL, and ACaL have not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of research since its first diagnostic description, 2 subtalar joint instability remains a clinical enigma within the concept of hindfoot instability 9 . This could be attributed to the complex anatomy, 37,38 triplanar motion, 39 and clinical presentation, 9 which is difficult to discern from ankle instability due to overlapping symptomology 40 . For this reason, diagnostic imaging holds an important potential to characterize subtalar joint instability.…”
Section: Discussionmentioning
confidence: 99%